Ultra-high strength steel plate with excellent thermal stability and high yield ratio and its manufacturing method

By optimizing the composition and manufacturing process of ultra-high strength steel sheets, the steel achieves excellent thermal stability and maintains high strength even after heat treatment at relatively low temperatures, addressing the thermal instability issues in existing steel sheets.

JP7662794B2Active Publication Date: 2025-04-15POHANG IRON & STEEL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023537431
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-21
Filing Date
2021-11-18
Publication Date
2025-04-15
Estimated Expiration
2041-11-18

AI Technical Summary

Technical Problem

Existing ultra-high strength steel sheets experience a decrease in strength and durability due to thermal instability when heated, leading to poor formability and durability, especially when exposed to temperatures below 600°C.

Method used

A steel sheet composition with specific weight percentages of elements such as C, Si, Mn, Cr, Mo, Ti, Nb, V, and B, along with a manufacturing process involving reheating, hot rolling, and controlled cooling, is used to achieve a microstructure with 60-90% martensite, 10-40% bainite, and 5% or less ferrite, ensuring a yield ratio of 0.8 or more and tensile strength of 950 MPa or more.

Benefits of technology

The resulting steel sheet exhibits excellent thermal stability, maintaining over 80% of its tensile strength after heat treatment at 400-600°C, and provides a high yield ratio and ultra-high strength properties suitable for a wide range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662794000001
    Figure 0007662794000001
  • Figure 0007662794000002
    Figure 0007662794000002
  • Figure 0007662794000003
    Figure 0007662794000003
Patent Text Reader

Abstract

The present invention relates to an ultra-high strength steel plate and a manufacturing method thereof. More specifically, the present invention provides a steel plate having excellent thermal stability and a high yield ratio and ultra-high strength even after heat treatment at a relatively low temperature, and a manufacturing method thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ultra-high strength steel plate and a manufacturing method thereof, and more particularly to an ultra-high strength steel plate having excellent thermal stability and a high yield ratio, and a manufacturing method thereof. [Background technology]

[0002] Steel plates used in boom arms for heavy equipment, frames and reinforcements for commercial vehicles, and structural members of building and machine parts may be heated partially or entirely for various purposes during manufacturing and use. For example, commercial vehicle frames and reinforcements often require local shape adjustments for bonding with parts, and for this reason, local heating and deformation may be applied to the steel. However, there is a problem that the strength of the steel changes due to such heating processes, resulting in poor durability. This is because the carbon in solid solution is rearranged during the heating process, or clustering is formed at dislocations, grain boundaries, etc., to form carbides, which induces brittleness of the steel. Furthermore, microstructures such as martensite, bainite, and retained austenite in the steel also change, causing a sudden change in the strength of the steel and affecting its formability and durability.

[0003] As described above, the changes in the structure and physical properties of steel during the heating process differ depending on the initial steel's composition and microstructure, and are highly dependent on heat treatment conditions such as heating temperature and holding time. However, until now, the focus has been only on preventing the deterioration of strength at high temperatures of 600°C or higher.

[0004] For example, Patent Documents 1 and 2 propose a technique for adding Cr, Mo, Nb, V, etc. as alloying elements and using tempering after hot rolling to ensure high-temperature strength, but this is merely a technique suitable for manufacturing thick steel plates for construction. In addition, when considering the environmental factor that construction steel is inevitably heated by fire, etc., adding a large amount of alloying elements such as Cr, Mo, Nb, V, etc. in the steel can ensure a certain level of strength even when exposed to a high-temperature environment of 600°C or higher for a long time, but on the other hand, there is a problem that manufacturing costs are excessive, such as the need to perform tempering. In particular, when used for short-term exposure to an environment of 600°C or lower, there is a disadvantage that the thermal stability is excessive.

[0005] Patent Document 3 describes a technique for adding Ti, Nb, Cr, Mo, etc. to ensure the strength of the portion that is affected by heat during welding, and is suitable for suppressing softening in the adjacent portion of the weld when welding automotive structural members. However, this technique has a limitation in that the portion adjacent to the weld material melted by the welding heat during arc welding is heated to a high temperature of 600°C or more, and may be heated to a temperature above the austenite region in particular.

[0006] Patent Document 4 is a technology that ensures high-temperature strength by adding Cr, Mo, Ti, Nb, V, etc., and, like the above technology, ensures strength when exposed to high temperatures of 600°C or higher for a long period of time. However, when manufactured under given composition and manufacturing conditions, the tensile strength (TS) is only at the 530 MPa level, which is different from giga-class ultra-high strength steels in terms of use and strength. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Korean Patent Registration No. 10-0358939 (Announced on October 16, 2002) [Patent Document 2] Korean Patent Registration No. 10-1290382 (Announced on 2013.07.22) [Patent Document 3] Korean Patent Registration No. 10-0962745 (Announced 2010.06.03) [Patent Document 4] Korean Patent Registration No. 10-1246390 (Announced on March 21, 2013) Summary of the Invention [Problem to be solved by the invention]

[0008] One aspect of the present invention is to provide a steel sheet which is excellent in thermal stability and has a high yield ratio and ultra-high strength even after heat treatment at a relatively low temperature, and a manufacturing method thereof.

[0009] The subject of the present invention is not limited to the above-mentioned contents. A person skilled in the art will have no difficulty in understanding further subjects of the present invention from the overall content of this specification. [Means for solving the problem]

[0010] According to one aspect of the present invention, the alloy contains, by weight percent, 0.05-0.13% C, 0.01-0.5% Si, 0.8-2.0% Mn, 0.005-1.2% Cr, 0.001-0.5% Mo, 0.001-0.02% P, 0.001-0.01% S, 0.01-0.1% Al, 0.001-0.01% N, 0.001-0.01% Ti, 0.001-0.03% Nb, 0.001-0.2% V, 0.0003-0.003% B, with the balance being Fe and unavoidable impurities, The K value defined by the following relational formula 1 is -1.05 or more, The G value defined by the following relational formula 2 is 2 to 20, The microstructure contains, by area percent, 60-90% martensite (including tempered martensite), 10-40% bainite, and less than 5% ferrite. It is possible to provide a steel sheet having a yield ratio of 0.8 or more. [Equation 1] K=-0.6-1.42[C]+0.05[Si]-0.16[Mn]-0.08[Cr]-0.03[Mo]+0.09[Ti]+0.08[Nb] 2 (Here, [C], [Si], [Mn], [Cr], [Mo], [Ti] and [Nb] are the weight percentages of the corresponding alloying elements.) [Equation 2] G=([Nb] / 93+[Mo] / 96+[V] / 51) / ([Ti] / 48) (Here, [Nb], [Mo], [V] and [Ti] are the weight percentages of the corresponding alloying elements.)

[0011] The steel plate may have a tensile strength of 950 MPa or more.

[0012] The above steel sheet may have a tensile strength after heat treatment at 400 to 600° C. that is 80% or more of the tensile strength before the heat treatment.

[0013] Another aspect of the present invention is a step of reheating a steel slab containing, by weight, 0.05-0.13% C, 0.01-0.5% Si, 0.8-2.0% Mn, 0.005-1.2% Cr, 0.001-0.5% Mo, 0.001-0.02% P, 0.001-0.01% S, 0.01-0.1% Al, 0.001-0.01% N, 0.001-0.01% Ti, 0.01-0.05% Nb, 0.001-0.03% V, 0.001-0.2% B, the balance being Fe and unavoidable impurities, and having a K value defined by the following relational formula 1 of -1.05 or more and a G value defined by the following relational formula 2 of 2-20; hot rolling the reheated steel slab; and The hot-rolled steel sheet may be primarily cooled to a temperature range of 300-500°C at a cooling rate of 60°C / s or more, and then secondarily cooled to a temperature range of 50-200°C at a cooling rate of 10-70°C / s, followed by coiling. [Equation 1] K=-0.6-1.42[C]+0.05[Si]-0.16[Mn]-0.08[Cr]-0.03[Mo]+0.09[Ti]+0.08[Nb] 2 (Here, [C], [Si], [Mn], [Cr], [Mo], [Ti] and [Nb] are the weight percentages of the corresponding alloying elements.) [Equation 2] G=([Nb] / 93+[Mo] / 96+[V] / 51) / ([Ti] / 48) (Here, [Nb], [Mo], [V] and [Ti] are the weight percentages of the corresponding alloying elements.)

[0014] The reheating temperature in the reheating step is 1150 to 1350 ° C. The rolling end temperature in the hot rolling step may be 850 to 1150°C.

[0015] During the cooling, the secondary cooling rate may be 60° C. or less. Effect of the Invention

[0016] According to one aspect of the present invention, it is possible to provide a steel sheet which has excellent thermal stability and has a high yield ratio and ultra-high strength even after heat treatment at a relatively low temperature, and a manufacturing method thereof.

[0017] According to another aspect of the present invention, it is possible to provide an ultra-high strength steel sheet and a method for producing the same that can be used in a wide range of applications because heat treatment can be performed at a relatively low temperature in a short period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, preferred embodiments of the present invention will be described. The embodiments of the present invention can be modified in various ways, and the scope of the present invention should not be construed as being limited to the embodiments described below. The present embodiments are provided to further explain the present invention in detail to those skilled in the art to which the present invention pertains.

[0019] In order to solve the problems of the conventional technology described above, the present inventors measured the change in room temperature tensile strength of steels having various components and microstructures after heat treatment in the temperature range of 400 to 600°C, and confirmed that the change in tensile strength depends on the slope of the dynamic strength value measured while the steel material is being heated.

[0020] From the results, the inventors were able to derive Relational Equations 1 and 2 for optimizing the contents of the main components of steel, namely, C, Mn, Si, Cr, Mo, Ti, Nb, and V. They also confirmed that excellent thermal stability can be ensured by controlling the conditions of the manufacturing process, and thus completed the present invention.

[0021] The present invention will be described in detail below.

[0022] The steel composition of the present invention will be described in detail below.

[0023] In the present invention, unless otherwise specified, % representing the content of each element is based on weight.

[0024] A steel sheet according to one aspect of the present invention contains, by weight, C: 0.05-0.13%, Si: 0.01-0.5%, Mn: 0.8-2.0%, Cr: 0.005-1.2%, Mo: 0.001-0.5%, P: 0.001-0.02%, S: 0.001-0.01%, Al: 0.01-0.1%, N: 0.001-0.01%, Ti: 0.01-0.05%, Nb: 0.001-0.03%, V: 0.001-0.2%, B: 0.0003-0.003%, with the balance being Fe and unavoidable impurities.

[0025] Carbon (C): 0.05~0.13% Carbon (C) is the most economical and effective element for strengthening steel, and as the amount of carbon added increases, the tensile strength increases due to an increase in the martensite or bainite fraction. If the carbon (C) content is less than 0.05%, it is difficult to obtain the above-mentioned effects sufficiently, and if the carbon (C) content exceeds 0.13%, the strength of martensite increases due to the excess carbon (C), but the solid solution strengthening effect of carbon (C) may be greatly reduced during heat treatment in the 400 to 600°C range.

[0026] Therefore, the carbon (C) content may be 0.05 to 0.13%, with a more preferable lower limit being 0.07% and a more preferable upper limit being 0.11%.

[0027] Silicon (Si): 0.01 to 0.5% Silicon (Si) is an element that has the effect of deoxidizing molten steel, strengthening the solid solution, and delaying the formation of coarse carbides, thereby improving formability. If the silicon (Si) content is less than 0.01%, it is difficult to obtain the above-mentioned effects, whereas if the silicon (Si) content exceeds 0.5%, red scale due to silicon (Si) is formed on the steel sheet surface during hot rolling, resulting in a problem that not only the surface quality of the steel sheet is significantly deteriorated, but also the weldability is reduced.

[0028] Therefore, the content of silicon (Si) may be 0.01 to 0.5%, and a more preferable upper limit may be 0.3%.

[0029] Manganese (Mn): 0.8-2.0% Manganese (Mn), like Si, is an effective element for solid solution strengthening of steel, and it can increase the hardening ability of steel and facilitate the formation of martensite and bainite during cooling after heat treatment. If the manganese (Mn) content is less than 0.8%, the above effects of addition cannot be obtained, and if the content exceeds 2.0%, it is advantageous for ensuring early strength, but there is a possibility that the difference between the initial strength and the strength after heat treatment will become large during heat treatment in the range of 400 to 600°C. In addition, during slab casting in the continuous casting process, segregation develops significantly in the center of the thickness, inducing deviation, and MnS is easily formed, which may result in poor ductility.

[0030] Therefore, the manganese (Mn) content may be 0.8 to 2.0%, with a more preferable lower limit being 1.0% and a more preferable upper limit being 1.8%.

[0031] Chromium (Cr): 0.005~1.2% Chromium (Cr) strengthens the steel through solid solution and delays the ferrite transformation during cooling, helping to form martensite and bainite. It also contributes to strength after heat treatment by precipitating fine composite carbides with Mo, Ti, Ni, etc. If the chromium (Cr) content is less than 0.005%, the above effects of adding it cannot be obtained, and if the content exceeds 1.2%, similar to Mn, the segregation area develops significantly in the center of the thickness, making the microstructure in the thickness direction non-uniform and possibly causing a disadvantage in terms of alloy cost.

[0032] Therefore, the chromium (Cr) content may be 0.005 to 1.2%, and a more preferable lower limit may be 0.4%.

[0033] Molybdenum (Mo): 0.001~0.5% Molybdenum (Mo) increases the hardening ability of steel and facilitates the formation of martensite and bainite. It also forms fine Nb-Ti-Mo carbides during heat treatment, mitigating strength loss. If the content of Mo is less than 0.001%, the above effects of adding it cannot be obtained, and if the content exceeds 0.5%, it may be economically disadvantageous.

[0034] Therefore, the molybdenum (Mo) content may be 0.001 to 0.5%, with a more preferable lower limit being 0.05% and a more preferable upper limit being 0.3%.

[0035] Phosphorus (P): 0.001 to 0.02% Phosphorus (P) has a solid solution strengthening effect, but can cause brittleness due to grain boundary segregation. Manufacturing with a phosphorus (P) content of less than 0.001% is economically disadvantageous because of the high manufacturing costs, and is insufficient for obtaining strength. On the other hand, if the content exceeds 0.02%, brittleness occurs due to grain boundary segregation, fine cracks are likely to occur during molding, and ductility and impact resistance properties can be significantly deteriorated.

[0036] Therefore, the phosphorus (P) content can be 0.001 to 0.02%.

[0037] Sulfur (S): 0.001-0.01% Sulfur (S) is an impurity present in steel, and if its content exceeds 0.01%, it combines with Mn and other substances to form non-metallic inclusions, which can cause fine cracks to occur when the steel is cut, significantly reducing impact resistance. On the other hand, reducing the sulfur (S) content to less than 0.001% takes a lot of time during steelmaking operations, which can reduce productivity.

[0038] Therefore, the sulfur (S) content can be 0.001 to 0.01%.

[0039] Aluminum (Al): 0.01 to 0.1% Aluminum (Al) is added mainly for deoxidation. If the content of aluminum (Al) is less than 0.01%, the above-mentioned effect of addition is insufficient, and if the content exceeds 0.1%, Al combines with N to form AlN, which may cause corner cracks in the slab during continuous casting and defects due to the formation of inclusions.

[0040] Therefore, the content of aluminum (Al) may be 0.01 to 0.1%, with a more preferable lower limit being 0.02% and a more preferable upper limit being 0.05%.

[0041] Nitrogen (N): 0.001-0.01% Nitrogen (N), along with C, is a representative solid solution strengthening element, and forms coarse precipitates along with Ti, Al, etc. In general, the solid solution strengthening effect of nitrogen (N) is superior to that of C, but as the amount of nitrogen (N) in steel increases, the toughness decreases significantly, so the upper limit is limited to 0.01%. On the other hand, reducing the content to less than 0.001% requires excessive time during steelmaking operations, which reduces productivity.

[0042] Therefore, the nitrogen (N) content can be 0.001 to 0.01%.

[0043] Titanium (Ti): 0.01-0.05% Titanium (Ti), along with Nb, Mo, and V, is a typical precipitation strengthening element, and contributes to the role of mitigating the decrease in strength due to the formation of carbides after heat treatment. However, the effect is inferior because the precipitate formation temperature is higher than that of other precipitation elements. In addition, it forms coarse TiN due to its strong affinity with N. Such TiN has the effect of suppressing grain growth during the heating process for hot rolling, and is advantageous in utilizing B, which is added to stabilize solute N and improve hardening ability. If the titanium (Ti) content is less than 0.01%, it is difficult to obtain the above effect, and if the content exceeds 0.05%, there is a problem that the low-temperature impact resistance is deteriorated due to the generation of coarse TiN and the coarsening of precipitates during heat treatment.

[0044] Therefore, the titanium (Ti) content may be 0.01 to 0.05%, and a more preferable upper limit may be 0.03%.

[0045] Niobium (Nb): 0.001-0.03% Niobium (Nb) is a representative precipitation strengthening element along with Ti and V, and is effective in improving the strength and impact toughness of steel by forming carbides during hot rolling and refining the crystal grains by delaying recrystallization. The formation of carbides reduces the C content in steel, which reduces the strength reduction effect caused by C during heat treatment in the 400 to 600°C range. If the niobium (Nb) content is less than 0.001%, the above effect cannot be obtained, and if the content exceeds 0.03%, the precipitates formed during rolling excessively delay recrystallization, which may result in poor anisotropy of the steel.

[0046] Therefore, the niobium (Nb) content can be 0.001 to 0.03%, and a more preferable upper limit can be 0.02%.

[0047] Vanadium (V): 0.001 to 0.2% Vanadium (V) is a strong precipitation hardening element, and active precipitation occurs in the reheating temperature range. It is an element that can compensate for the decrease in strength caused by annealing martensite by forming precipitates during reheating, and it is preferable to add vanadium (V) at a content of 0.001% or more, but if the content exceeds 0.2%, it may be economically disadvantageous.

[0048] Therefore, the vanadium (V) content can be 0.001 to 0.2%.

[0049] Boron (B): 0.0003 to 0.003% Boron (B) delays ferrite transformation and is advantageous in ensuring early strength due to bainite and martensite. When present in a solid solution state in steel, it has the effect of stabilizing grain boundaries and improving the brittleness of steel at low temperatures, and since it forms BN together with solute N, it can suppress the formation of coarse nitrides. If the boron (B) content is less than 0.0003%, it is difficult to obtain the above effect, and if the content exceeds 0.003%, it contributes to improving the initial strength, but does not contribute significantly to improving the strength after heat treatment, and the strength after heat treatment may decrease significantly.

[0050] Therefore, the content of boron (B) can be 0.0003 to 0.003%.

[0051] The steel sheet of the present invention may contain the remaining iron (Fe) and inevitable impurities in addition to the above-mentioned composition. The inevitable impurities may be mixed in unintentionally during normal manufacturing processes, and therefore cannot be excluded. These impurities are known to any engineer in the field of normal steel manufacturing, and therefore all of the contents thereof will not be specifically mentioned in this specification.

[0052] The steel sheet of the present invention can have a K value defined by the following relational expression 1 of -1.05 or more.

[0053] The thermal stability of steel, which is related to the K value in the relational expression 1, is based on the deformation resistance of the steel to an external force applied to the steel at a given temperature. As an example, a high-temperature compression test or a high-temperature tensile test is performed on a steel material, and during the test, the material is heated at a constant heating rate while an external force is applied at a constant deformation rate to measure the force acting per unit area of ​​the material. In this way, the slope value of the measured stress-temperature curve is regarded as the thermal stability, which can be regarded as an inherent characteristic of the steel material.

[0054] In this invention, the measurement was performed by applying a high-temperature compression test method, in which the steel material was heated to 600°C at a temperature increase rate of 1°C / s, and simultaneously a 30% deformation was applied at a deformation rate of 0.005 / s. The slope K of the obtained stress-temperature curve was obtained for various steel materials, and the relational expression 1 was derived.

[0055] If the K value in the above-mentioned relational expression 1 is less than -1.05, the thermal stability is insufficient, and the change in strength before and after the heat treatment at 100 to 600°C may increase. In particular, such a change in yield strength before and after the heat treatment tends to be more stable when the relational expression 2 is also satisfied. More preferably, the K value can be -1.03 or more. [Equation 1] K=-0.6-1.42[C]+0.05[Si]-0.16[Mn]-0.08[Cr]-0.03[Mo]+0.09[Ti]+0.08[Nb] 2 (Here, [C], [Si], [Mn], [Cr], [Mo], [Ti] and [Nb] are the weight percentages of the corresponding alloying elements.)

[0056] The steel sheet of the present invention may have a G value of 2 to 20, as defined by the following relational expression 2.

[0057] When Relational Expression 1 and Relational Expression 2 are satisfied simultaneously, the decrease in strength after heat treatment can be mitigated and thermal stability can be ensured.

[0058] The following relational expression 2 shows the relationship between the strength after heat treatment due to precipitates and the components, and relates to the formation of precipitates in fine grains generated during heat treatment. Precipitates have the effect of complementing the reduction in strengthening due to dislocations and solute carbon, but if the G value is less than 2, the formation of precipitates in the steel sheet after heat treatment may be insufficient, or the formation of coarse precipitates in the initial steel sheet may increase, reducing the formation of precipitates in fine grains generated during heat treatment, resulting in insufficient thermal stability. On the other hand, if the value exceeds 20, the effect of improving thermal stability decreases, and it may be economically disadvantageous because a large amount of expensive alloy elements must be added. It may be more preferably 3 or more, and more preferably 17 or less. [Equation 2] G=([Nb] / 93+[Mo] / 96+[V] / 51) / ([Ti] / 48) (Here, [Nb], [Mo], [V] and [Ti] are the weight percentages of the corresponding alloying elements.)

[0059] In the following, the steel microstructure of the present invention will be described in detail.

[0060] In the present invention, unless otherwise specified, the percentage indicating the fraction of the microstructure is based on the area.

[0061] The microstructure of the steel sheet according to one aspect of the present invention may contain, in area percentage, 60 to 90% martensite (including tempered martensite), 10 to 40% bainite, and 5% or less ferrite.

[0062] Martensite is a structure that is disadvantageous for ensuring thermal stability, but is necessary for ensuring initial strength. Strength can be ensured by the solid solution of C and lattice warping, but since the above effects disappear during heat treatment, very large changes in strength can occur.

[0063] If the martensite fraction exceeds 90%, the strength change after heat treatment is large and the strength after heat treatment is not satisfied, whereas if the fraction is less than 60%, the initial strength cannot be ensured. Bainite is less favorable than martensite for ensuring initial strength, but is an advantageous structure for strength change after heat treatment. In the present invention, the fraction of martensite is shown to include both tempered martensite and bainite.

[0064] If the bainite fraction exceeds 40%, the initial strength cannot be secured, and if the fraction is less than 10%, the strength change after heat treatment may be large. Also, although the microstructure may contain ferrite up to 5%, if the content exceeds 5%, it is disadvantageous in securing the initial strength.

[0065] The steel production method of the present invention will now be described in detail.

[0066] The steel according to one aspect of the present invention can be produced by reheating, hot rolling, cooling and coiling a steel slab satisfying the alloy composition described above.

[0067] Slab Reheat A steel slab satisfying the above-mentioned alloy composition can be reheated in the temperature range of 1150 to 1350°C.

[0068] If the reheating temperature is less than 1150°C, precipitate-forming elements such as Nb and Ti are not sufficiently redissolved, and the formation of precipitates is reduced during heat treatment of the manufactured steel sheet, leaving coarse TiN, and the generated segregation may be difficult to eliminate by diffusion during continuous casting.On the other hand, if the temperature exceeds 1350°C, abnormal grain growth of austenite grains may cause a decrease in strength and uneven structure.

[0069] Hot rolling The reheated steel slab can be hot rolled at a rolling finish temperature of 850 to 1150°C.

[0070] If the rolling end temperature exceeds 1150°C, the temperature of the hot-rolled steel sheet becomes too high, the grain size becomes coarse, and the final transformation structure may become non-uniform. On the other hand, if the temperature is less than 850°C, the recrystallization may be delayed too much, causing elongated grains to develop, resulting in severe anisotropy and poor formability. In particular, Nb carbides may be formed due to deformation-induced precipitation, which may be unfavorable to the formation of fine carbides during heat treatment.

[0071] Cooling and winding The hot-rolled steel sheet can be primarily cooled to a temperature range of 300 to 500°C at a cooling rate of 60°C / s or more, and secondarily cooled to a temperature range of 50 to 200°C at a cooling rate of 10 to 70°C / s, and then coiled.

[0072] In the present invention, the microstructure is optimized to ensure the desired physical properties, and in order to achieve this, the cooling process can be divided into two stages.

[0073] If the cooling rate during the primary cooling is less than 60°C / s, ferrite may form, which may reduce the strength of the steel sheet. Also, if the primary cooling end temperature exceeds 500°C, ferrite will form and the initial strength of the steel sheet will decrease, while if the temperature is less than 300°C, it will be difficult to form bainite in the steel sheet, which is advantageous for ensuring initial strength, but there is a possibility that the strength will decrease significantly after heat treatment.

[0074] In the secondary cooling, when the temperature is cooled to a range of 50 to 200°C, auto-tempering occurs and fine carbides are precipitated. This reduces the initial tensile strength, but increases the yield strength and has a high yield ratio, which has the effect of mitigating the strength drop during heat treatment. If the cooling end temperature during the secondary cooling is less than 50°C, auto-tempering does not occur and the strength drop after heat treatment is large, and if the temperature exceeds 200°C, the auto-tempering effect becomes excessive, carbides become coarse, the brittleness of the steel may increase, and fine precipitation of Nb and Ti may be affected at high temperatures. More preferably, the secondary cooling rate may be 10 to 60°C / s. If the secondary cooling rate exceeds 70°C / s, auto-tempering does not occur, the yield ratio is low, and the initial tensile strength is high, which may result in a large drop in strength after heat treatment. On the other hand, if the cooling rate is less than 10°C / s, there is a problem that the auto-tempering effect becomes excessive.

[0075] The steel of the present invention manufactured as described above has a tensile strength of 950 MPa or more, a yield ratio of 0.8 or more, and a tensile strength after heat treatment at 400 to 600°C that is 80% or more of the tensile strength before heat treatment, and can have the properties of a high yield ratio and ultra-high strength while having excellent thermal stability.

[0076] The present invention will be described in more detail below with reference to examples. However, it should be noted that the following examples are merely intended to illustrate and explain the present invention in more detail, and are not intended to limit the scope of the present invention. EXAMPLES

[0077] Table 1 below shows the alloying composition by steel type and the results of calculating Relation 1 and Relation 2 based on the alloying composition. For each steel type in Table 1, steel sheets were manufactured under the conditions shown in Table 2. Table 2 also shows the rolling end temperature, primary and secondary cooling end temperatures, and primary and secondary cooling rates. The reheating temperature not shown in Table 2 below was 1250°C, and the thickness of the steel material after hot rolling was the same for all steel types, 3 mm.

[0078] [Table 1]

[0079] [Equation 1] K=-0.6-1.42[C]+0.05[Si]-0.16[Mn]-0.08[Cr]-0.03[Mo]+0.09[Ti]+0.08[Nb] 2 (Here, [C], [Si], [Mn], [Cr], [Mo], [Ti] and [Nb] are the weight percentages of the corresponding alloying elements.) [Equation 2] G=([Nb] / 93+[Mo] / 96+[V] / 51) / ([Ti] / 48) (Here, [Nb], [Mo], [V] and [Ti] are the weight percentages of the corresponding alloying elements.)

[0080] [Table 2]

[0081] Table 3 below shows the microstructure and mechanical properties of the steel sheets produced. The fractions of ferrite, bainite, and martensite were measured and shown, and the tensile strength and yield ratio (yield strength / tensile strength) of the produced steels were also shown. The fraction of martensite is shown including the fraction of tempered martensite. The tensile strength of the produced steel sheets after heat treatment was also measured, and the ratio to the tensile strength before heat treatment was shown. The heat treatment was performed by heating to 500°C and maintaining it for 15 minutes. For the tensile test, JIS No. 5 standard test pieces were taken in a direction parallel to the rolling direction and tested, and the microstructure was measured at 1 / 4 of the thickness of each steel type and was measured from the results of analysis using a SEM at magnifications of x3000 and x5000.

[0082] [Table 3]

[0083] As shown in Table 3, the invention steels 1 to 6, which satisfy the alloy composition and manufacturing method proposed in the present invention, ensured all of the mechanical properties targeted in the present invention.

[0084] On the other hand, the C contents of Comparative Steels 1 and 2 were outside the range of the present invention, and Comparative Steel 1 did not reach the C content of the present invention, so the microstructure targeted by the present invention could not be secured, resulting in insufficient tensile strength. Comparative Steel 2 had an excessive C content outside the range of Relation 1, so the ratio of tensile strength before and after heat treatment did not satisfy the requirement.

[0085] The Mn contents of Comparative Steels 3 and 4 were outside the range of the present invention, and Comparative Steel 3 exceeded the Mn content of the present invention and did not satisfy Relation 1. As a result, a fine structure could not be obtained and the yield ratio was deteriorated. Comparative Steel 4 had an insufficient Mn content, making it difficult to obtain the fine structure proposed in the present invention, and as a result, the tensile strength was also insufficient.

[0086] Comparative steels 5 and 6 did not satisfy the cooling conditions during the first cooling. Comparative steel 5 exceeded the range of the cooling end temperature, and comparative steel 6 had an insufficient cooling rate. As a result, the microstructure targeted by the present invention was not achieved, and the strength was insufficient.

[0087] In Comparative Steel 7, the secondary cooling rate was exceeded, and martensite was formed excessively. As a result, the yield ratio was not achieved, and the change in tensile strength before and after the heat treatment was large, so that the tensile strength ratio did not satisfy the range of the present invention.

[0088] Comparative steel 8 did not satisfy Relational formula 2, and the change in tensile strength before and after the heat treatment was large, so that the ratio of tensile strength before and after the heat treatment proposed in the present invention was not satisfied.

[0089] In Comparative Steel 9, the primary cooling end temperature was too low, resulting in excessive formation of martensite, which resulted in an insufficient yield ratio and an excessive change in tensile strength before and after heat treatment.

[0090] In Comparative Steel 10, the secondary cooling end temperature was lower than the temperature range proposed in the present invention, and auto-tempering was excessive, which resulted in an insufficient yield ratio and failure to satisfy the ratio of tensile strength before and after heat treatment.

[0091] Although the present invention has been described in detail with reference to the above exemplary embodiments, other embodiments may be possible, and therefore the scope of the appended claims should not be limited to the exemplary embodiments.

Claims

1. The alloy comprises, by mass%, C: 0.05-0.13%, Si: 0.01-0.5%, Mn: 0.8-2.0%, Cr: 0.005-1.2%, Mo: 0.001-0.5%, P: 0.001-0.02%, S: 0.001-0.01%, Al: 0.01-0.1%, N: 0.001-0.01%, Ti: 0.01-0.05%, Nb: 0.001-0.03%, V: 0.001-0.2%, B: 0.0003-0.003%, with the balance being Fe and unavoidable impurities; The K value defined by the following relational formula 1 is -1.05 or more, The G value defined by the following relational formula 2 is 2 to 20, The microstructure contains, by area percent, 60-80% martensite (including tempered martensite), 20-40% bainite, and 5% or less ferrite; A steel plate having a yield ratio of 0.8 or more. [Relationship 1] K=-0.6-1.42[C]+0.05[Si]-0.16[Mn]-0.08[Cr]-0.03[Mo]+0.09[Ti]+0.08[Nb] 2 (Here, [C], [Si], [Mn], [Cr], [Mo], [Ti] and [Nb] are the mass% of the corresponding alloying elements.) [Relationship 2] G=([Nb] / 93+[Mo] / 96+[V] / 51) / ([Ti] / 48) (Here, [Nb], [Mo], [V] and [Ti] are the mass% of the corresponding alloying elements.)

2. The steel plate according to claim 1, wherein the steel plate has a tensile strength of 950 MPa or more.

3. The steel plate according to claim 1, wherein the tensile strength of the steel plate after heat treatment at 400 to 600° C. is 80% or more of the tensile strength before the heat treatment.

4. reheating a steel slab containing, by mass%, C: 0.05-0.13%, Si: 0.01-0.5%, Mn: 0.8-2.0%, Cr: 0.005-1.2%, Mo: 0.001-0.5%, P: 0.001-0.02%, S: 0.001-0.01%, Al: 0.01-0.1%, N: 0.001-0.01%, Ti: 0.01-0.05%, Nb: 0.001-0.03%, V: 0.001-0.2%, B: 0.0003-0.003%, with the balance being Fe and unavoidable impurities, and having a K value defined by the following relational formula 1 of -1.05 or more and a G value defined by the following relational formula 2 of 2-20; hot rolling the reheated steel slab; and The method for producing a steel sheet according to any one of claims 1 to 3, further comprising the steps of primarily cooling the hot-rolled steel sheet to a temperature range of 300 to 500°C at a cooling rate of 60°C / s or more, secondary cooling to a temperature range of 50 to 200°C at a cooling rate of 10 to 60°C / s, and then coiling the steel sheet. [Relationship 1] K=-0.6-1.42[C]+0.05[Si]-0.16[Mn]-0.08[Cr]-0.03[Mo]+0.09[Ti]+0.08[Nb] 2 (Here, [C], [Si], [Mn], [Cr], [Mo], [Ti] and [Nb] are the mass% of the corresponding alloying elements.) [Relationship 2] G=([Nb] / 93+[Mo] / 96+[V] / 51) / ([Ti] / 48) (Here, [Nb], [Mo], [V] and [Ti] are the mass% of the corresponding alloying elements.)

5. The reheating temperature in the reheating step is 1150 to 1350° C., The method for producing a steel sheet according to claim 4, wherein the rolling finish temperature in the hot rolling step is 850 to 1150°C.

Citation Information

Patent Citations

  • Method for manufacturing steel for construction with tensile strength of 58 kgf / mm¬2 class

    KR100358939B1

  • High strength steel sheet exhibiting good burringworkability and excellent resistance to softening inheat-affected zone and method for production thereof

    KR100962745B1

  • Fire-resistant steel and method of manufacturing the fire-resistant steel

    KR101246390B1

  • High strength structural steel and method of manufacturing the structural steel

    KR101290382B1

  • High-strength, hot rolled abrasive wear resistant steel strip

    US20200157651A1